DensiTree: Making sense of sets of phylogenetic trees - Bouckaert, Remco R. (Bioinformatics, 2010)
Bayesian analysis through programs like BEAST (Drummond and Rumbaut, 2007) and MrBayes (Huelsenbeck et al., 2001) provides a powerful method for reconstruction of evolutionary relationships. One of the benefits of Bayesian methods is that well-founded estimates of uncertainty in models can be made available. So, for example, not only the mean time of a most recent common ancestor (tMRCA) is estimated, but also the spread. This distribution over model space is represented by a set of trees, which can be rather large and difficult to interpret. DensiTree is a tool that helps navigating these sets of trees. The main idea behind DensiTree is to draw all trees in the set transparently. As a result, areas where a lot of the trees agree in topology and branch lengths show up as highly colored areas, while areas with little agreement show up as webs. This makes it possible to quickly get an impression of properties of the tree set such as well-supported clades, distribution of tMRCA and areas of topological uncertainty. Thus, DensiTree provides a quick method for qualitative analysis of tree sets.